2013
DOI: 10.1071/ah13005
|View full text |Cite
|
Sign up to set email alerts
|

Do people with existing chronic conditions benefit from telephone coaching? A rapid review

Abstract: Objective. To examine the effectiveness of telephone-based coaching services for the management of patients with chronic diseases.Methods. A rapid scoping review of the published peer reviewed literature, using Medline, Embase, CINAHL, PsychNet and Scopus. We included studies involving people aged 18 years or over with one or more of the following chronic conditions: type 2 diabetes, congestive cardiac failure, coronary artery disease, chronic obstructive pulmonary disease and hypertension. Patients were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 45 publications
0
82
0
3
Order By: Relevance
“…Th e review by Dennis et al (16) of telephone interventions concluded that unscripted (patient-centred) interventions appeared to be most eff ective for improving self-management skills in people from vulnerable groups and that planned (scheduled) calls helped promote relationships between patients and their health service provider. Th us the telephone support was both scheduled to occur at certain pre-determined time points and was also unscripted, i.e., individualized to the patient.…”
Section: Description Of the Interventionmentioning
confidence: 98%
“…Th e review by Dennis et al (16) of telephone interventions concluded that unscripted (patient-centred) interventions appeared to be most eff ective for improving self-management skills in people from vulnerable groups and that planned (scheduled) calls helped promote relationships between patients and their health service provider. Th us the telephone support was both scheduled to occur at certain pre-determined time points and was also unscripted, i.e., individualized to the patient.…”
Section: Description Of the Interventionmentioning
confidence: 98%
“…Telefoncoaching scheint laut einer australischen Studie bei chronischen Krankheiten wie Typ-2-Diabetes, Herzinsuffizienz, koronarer Herzkrankheit, chronisch obstruktiver Lungenkrankheit und Bluthochdruck Gesundheitsverhalten, Selbstwirksamkeit und den Gesundheitszustand zu verbessern [7]. Zum Nachweis des klinischen Nutzens bei Depression bedarf es weiterer Forschung [8][9][10][11].…”
Section: Hintergrund Und Fragestellungunclassified
“…Auch die Debeka Krankenversicherung berichtete über positive Ergebnisse eines Telefoncoachings, das in Zusammenarbeit mit einem professionellen Dienstleister durchgeführt wurde [19]. Somit können neben den von Dennis et al [7] in ihrem Review berücksichtigten somatischen chronischen Krankheiten auch depressiv Kranke von einem Telefoncoaching profitieren [12]. Weitere Studien sind unterwegs [9][10][11].…”
Section: Diskussionunclassified
“…This may be a simple and effective option to improve flexibility for some patients within WHPPs. 16,17 Our survey also showed that patients may desire general diet and weight management coaching over fitness related coaching within this FNWM coaching program. The topic of vitamins and supplements was also popular among respondents.…”
Section: Innovations In Pharmacymentioning
confidence: 99%
“…People may not be aware of the potential improvement in self-efficacy and health outcomes associated with health coaching. 16,18 Additionally, when examining successful WHPPs, those with comprehensive interventions, such as utilizing various wellness methods together, have increased participation and better outcomes. 19 Educating patients on the potentially synergistic benefits of multilevel approaches, such as using a coaching program along with other wellness methods, could help overcome this barrier to participation.…”
Section: Innovations In Pharmacymentioning
confidence: 99%